The European Heritage from a Critical Cosmopolitian Perspective - Gerard Delanty (London School of Economics and Political Science (LSE), European Institute, 2010)
The question of the European cultural heritage and the wider historical legacy of Europe has been the subject of much discussion in recent years as is reflected in new approaches to memory and commemoration, values, and European identity. Unlike earlier histories, which generally contained a 'grand narrative,' new histories of Europe are now generally more cautious in their assumptions about a continuity or a narrative based on the advancement of civilization. The general trend is towards a greater recognition of rupture, which must be measured against continuity, a unity in diversity and a certain problematization of the received values of tradition. This paper looks at various models for theorizing the European heritage in the wake of the end of the Grand Narrative accounts and makes the case for a critical cosmopolitan approach.
Keywords: 330